A megkésett nagyszabású vasúthálózat-bővítés politikai okai Kelet-Közép-Európa két államában - Erdősi, Ferenc (Közép-Európai Közlemények, 2015)
By the start of World War I the railway networks of developed and moderately developed Euro-pean countries had mostly been completed. In contrast, a common feature of the recently reborn Poland (founded on the territories previously belonging to Germany, Russia and the Austro-Hungarian Empire) and the Kingdom of SHS/Yugoslavia (which was synthesized from half-dozen entities, primarily inhabited by southern Slavs) was that their railway networks were significantly growing during the interwar period and also in the decades following 1945. They were also out-standing in drastically reducing their networks in the 1960s and 1970s. This article explores the causes of two states’ characteristic railway policies and their impact factors. The author draws attention to the fact that hard and soft dictatorships had radically different views on the necessity of eliminating unprofitable railway branch lines.